Pemanfaatan Plaform Canva sebagai Media Pembelajaran Interaktif terhadap Peningkatan Kreativitas Digital - Ahla Syafana; Cahya Ranis Sholihatun Fitrah (Lembaga Pengembangan Kinerja Dosen, 2026)
Learning activities based on conventional printed media lacking attractive visual elements tend to cause student boredom and hinder their progress in digital technology. Departing from this issue, the purpose of this study, titled